Risk prediction model for serious infections in psoriasis. (1st April 2019) - Yiu, Z.Z.N.; Sorbe, C.; Lunt, M.; Rustenbach, S.J.; KÜhl, L.; Augustin, M.; Mason, K.J.; Ashcroft, D.M.; Griffiths, C.E.M.; Warren, R.B.
Summary: This study was carried out by a group of investigators from dermatology departments in Manchester and Hamburg. It used information from the German Psoriasis Registry and also the British Association of Dermatologists Biologic Interventions Register, or BADBIR, which collects information on the use and outcomes of new biologic drugs used for psoriasis. The team developed and then assessed a model for predicting which patients with psoriasis were most likely to develop severe infection within one year of starting systemically administered treatment (i.e. treatment that works on the whole body, rather than being applied just to the skin). The treatments assessed ranged from older methods where the drug is taken by mouth, such as methotrexate or ciclosporin, to the newer injected biologic therapies, such as etanercept or ustekinumab. Potential risk factors to be investigated, such as age, gender, disease severity and initial therapy, amongst others, were agreed by the assessment group. These serious infections were those where patients had prolonged admissions to hospital, were treated with intravenous antibiotics or where they died, within one year of starting these therapies. 1.7 % of both BADBIR and German patients developed a severe infection. Risk factors for a higher likelihood of serious infections included female gender, other underlying illnesses such as chronic lung disease, higher alcohol intake, and treatment with the biologic, infliximab. Interestingly age did not, by itself, pose a higher risk of infection. This work will prove very useful in helping dermatologists to decide which patients to treat, and with what drug, and to advise patients of lifestyle choices such as drinking alcohol.